2003
DOI: 10.1124/jpet.103.058008
|View full text |Cite
|
Sign up to set email alerts
|

Rosiglitazone Activates Renal Sodium- and Water-Reabsorptive Pathways and Lowers Blood Pressure in Normal Rats

Abstract: Synthetic agonists of the peroxisomal proliferator-activated receptor subtype ␥ (PPAR-␥) are highly beneficial in the treatment of type II diabetes. However, they are also associated with fluid retention and edema, potentially serious side effects of unknown origin. These studies were designed to test the hypothesis that rosiglitazone (RGZ, PPAR-␥ agonist) may activate sodium-and water-reabsorptive processes in the kidney, possibly in response to a drop in mean arterial blood pressure (MAP), as well as directl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
124
0
5

Year Published

2005
2005
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(142 citation statements)
references
References 37 publications
13
124
0
5
Order By: Relevance
“…Moreover, rosiglitazone-induced fluid retention and increased body weight was not associated with significant changes in plasma aldosterone or renal expression of the ENaC subunits ␣, ␤, and ␥, confirming previous reports. 15,18 Finally, treatment with rosiglitazone or pioglitazone did not significantly alter ENaC activity when directly assessed by patch-clamp analysis in split-open CDs of C57BL/6 mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, rosiglitazone-induced fluid retention and increased body weight was not associated with significant changes in plasma aldosterone or renal expression of the ENaC subunits ␣, ␤, and ␥, confirming previous reports. 15,18 Finally, treatment with rosiglitazone or pioglitazone did not significantly alter ENaC activity when directly assessed by patch-clamp analysis in split-open CDs of C57BL/6 mice.…”
Section: Discussionmentioning
confidence: 99%
“…18 Similarly, rosiglitazone was reported to increase whole-kidney protein abundance of the ␣ subunit of Na-K-ATPase as well as AQP2, whereas ENaC subunits were not affected; in addition, rosiglitazone increased the expression of the Na ϩ -H ϩ exchanger NHE3, the Na-K-2Cl co-transporter NKCC2, and AQP3. 15 These data indicate that activation of renal Na ϩ reabsorption pathways other than ENaC and of water reabsorption through water channels may also contribute to TZD-induced Na ϩ and fluid retention. Considering the diversity of results, an editorial concluded that the molecular mechanisms and the renal sites of action involved in TZD-induced fluid retention, including a role for ENaC in the CD, have not been clearly established.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…However, in addition to improved glycemic control, these agents cause weight gain, edema, and redistribution of body fat in individuals with type 2 diabetes (4 -6). Scarce animal and human data have suggested that renal sodium retention could be a causal factor for the development of fluid retention (7,8). Vascular endothelial growth factor (VEGF) also has been implicated as a causal factor in thiazolidinedione-induced edema (9).…”
mentioning
confidence: 99%
“…Such an effect has been repeatedly noted in other thiazolidinedione studies (12)(13)(14)(15)(16) and appears to be due to sodium and water retention at the renal collecting duct noted above, an increased plasma renin activity (17)(18)(19) perhaps related in part to a modest fall in blood pressure (20,21), and increased insulin action (20). Two echocardiographic studies (22,23) showed that rosiglitazone did not significantly reduce left systolic ventricular function.…”
Section: Renal Componentmentioning
confidence: 88%